Utilization of Ethanol Fermented Cassava Products in Laying Hen Rations - Wirachai Polrome; Usa Klinhom; Chusri Talabmook (Agriculture and Natural Resources, 1993)
The experiment was conducted to determine the effect of utilization of ethanol fermented cassava products (EFCP) with yeast cake in laying hen rations on performance and quality of products of laying hen (ISABROWN). EFCP was replaced for corn at levels of 0, 10, 20,30 and 40 percent of layer diets. Studying nutrient utilization of EFCP of laying hens by usnig completely randomized design and linear regression. The apparent metabolizable energy (AME) and apparent net protein utilization (ANPU) of the EFCP were 2229.85 Kcal/kg and 24.93 percent respectively. About the effects of EFCP on performance and quality products of laying hens, it was found that there was no significantly different in production performance between the controlled group and the groups fed with EFCP in the rations (P>0.05). But the cost of the EFCP rations was lower than that of the controlled group. As for the quality of eggs, there was no significant difference in weight of eggs, thickness of egg shell and haugh unit value of eggs between controlled group and the group fed with EFCP in the rations (P>0.05). Yolk colour of the EFCP fed groups was lighter than that of the controlled group (P<0.05).